Population Dynamics of the Root-knot Nematodes Meloidogyne incognita (Kofoid & White) Chitwood and M. javanica (Treub) Chitwood on Grapevines in two different Regions of South Africa - Loubser, J.T.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Two root-knot nematode species, Me/oidogyne incognita and M.javanica, were studied with regard to their seasonal population fluctuations on grapevines growing in two vastly different climatic areas. Regular observations on reproduction and numbers of larvae in the soil were compared with patterns of root growth, soil temperature and moisture. Population fluctuations of the two species showed similar trends in spite of the climatic differences in the two areas, but M. incognita in the northern Cape reached higher populations. Larvae populations in the soil declined in summer in both areas and increased during autumn to reach peaks in winter. With the onset of root growth in spring, larvae numbers decreased in the soil, as a result of large scale root penetration.